Canakinumab for the treatment of chronic obstructive pulmonary disease. (April 2015) - Rogliani, Paola; Calzetta, Luigino; Ora, Josuel; Matera, Maria Gabriella
Abstract: COPD is a preventable and treatable disease associated with an enhanced chronic inflammatory response. In addition to chronic inflammation other mechanisms have been proposed that is likely to be involved in the development and progression of COPD. Recent evidence in the literature suggests a role for the inflammasome in the airway inflammation observed in COPD. Inflammasomes are intracellular multiprotein complexes that facilitate the autoactivation of the proinflammatory caspase-1 that in response to specific signals induces ultimately the release of the mature form of the inflammatory cytokines IL-1β and IL-18. In stable COPD was observed a higher production of IL-1, with levels further increases during exacerbations. IL-1 is strongly expressed by macrophage-monocyte. It seems that the activity of IL-1β in the lung induces a phenotype with typical characteristics of COPD consisting of lung inflammation, emphysema, and airway fibrosis. COPD could benefit from a targeted approach to the suppression of the inflammatory response, although an effective anti-inflammatory treatment is not yet available. Canakinumab, an anti-IL-1β monoclonal antibody, that binds to human IL-1β with high specificity and neutralizes its signaling, resulting in suppression of inflammation in patients with disorders of autoimmune origin, has been recently evaluated in inflammatory conditions such as COPD.